Prevalence of previously undetected tuberculosis and underlying risk factors for transmission in a prison setting in Ibadan, south-western Nigeria (2014)
People with congregational tendencies such as the prison inmates constitute an important target group in the global efforts towards the control of tuberculosis (TB). The prison setting in most developing countries particularly Nigeria, currently does not have routine diagnostic procedures for TB despite the existing risks that could facilitate disease transmission. We conducted a cross sectional study among the inmates in a major prison in south-western Nigeria for TB by screening their sputum samples using a simple random sampling method coupled with questionnaire interview, on the assumption of sub-clinical pulmonary TB infection. The overall TB prevalence found was 1.2% (2/164). Significant risk factors that could facilitate disease transmission in the prison included lack of BCG immunization (p = 0.017); history of contact with TB patients (p = 0.020); prolonged cough (p = 0.016) and drug abuse (p = 0.019). Our findings of 1.2% undetected pulmonary TB infection among the inmates though low; still reiterate previous observation that the prison setting constitutes a veritable environment for TB transmission and a threat to public health. Efforts are therefore needed to institute routine screening and reduce the risk factors associated with TB transmission among prison inmates in Nigeria.